Investing into ETF – Exchange Investment Funds in Digital Economy - E. A. Shikhaleva; N. S. Mrochkovskiy (Вестник Российского экономического университета имени Г. В. Плеханова)
The article explains the notion of exchange investment funds as a tool of investing on stock exchange in conditions of digital economy. It studies attainable today tools for investing into exchange investment funds, structure, working mechanism, as well as goals and objectives of investment funds as a separate tool for investment. The authors identify the key aims of investing into investment funds available on the exchange and the sequence of using this investment tool. They show opportunities and threats of investing into exchange investment funds for the investor and necessary analytical tools for investing into exchange investment funds and also provide characteristics, which are essential for estimating and selecting investment funds by the investor. The article explains such terms as controlling company, liquidity, dividend yield, fund index, replication and demonstrates expediency of using tools of investing into investment funds for beginners and experienced investors. The authors research the present trends on the finance exchange in view of investing into exchange investment funds and come to the conclusion about basic preconditions for investing into investment funds.